Systematic analysis of ZDHHC9 as a potential prognostic and immunotherapy biomarker in breast cancer - Zhou, Desheng; Wu, Zhenpeng; Cui, Yachao; Wang, Doudou; Song, Hejun; Chen, Jun; Lin, Hong (Frontiers in Immunology, 2025)
BackgroundBreast cancer (BC) represents a highly heterogeneous malignancy and continues to be a leading source of death among women worldwide. Enhancing diagnostic and therapeutic approaches necessitates a thorough grasp of the underlying molecular pathways and the identification of dependable biomarkers. Although palmitoyl transferases, particularly ZDHHC9, have been associated with the progression of various cancers, their specific role in BC remains incompletely understood.MethodsIn this investigation, TCGA and GTEx databases were utilized to analyze the expression patterns of ZDHHC9 and to evaluate its prognostic significance. Moreover, the regulatory pathways involving ZDHHC9 were explored via co-expression analysis and differential gene enrichment studies. Insights into ZDHHC9 expression across different cell types and its potential oncogenic pathways were derived from scRNA sequencing analysis. Additionally, immunophenoscore (IPS), EaSIeR and immunotherapy cohorts were utilized to predict immunotherapy responses. The biological significance of ZDHHC9 was verified through in vitro and in vivo experiments.ResultsOur findings revealed that ZDHHC9 is markedly overexpressed in BC, with elevated levels of ZDHHC9 being correlated with poor survival outcomes, suggesting its role as an independent risk factor in BC. Furthermore, high ZDHHC9 expression was found to be associated with multiple immune cell types within BC. Notably, patients exhibiting lower ZDHHC9 expression demonstrated a higher likelihood of benefitting from immunotherapy. Lastly, the vivo and vitro experiments consistently demonstrated that suppression of ZDHHC9 expression could reduce BC cell proliferation.ConclusionsThis study highlights ZDHHC9 as a potential prognostic marker, a regulator of tumor immunity, and a biomarker of therapeutic response in BC, offering a promising avenue for improving BC diagnosis and treatment.